Alexander Mackenzie (1764-1820) - Davis, Richard C. (ARCTIC, 1987)
This profile recounts the two major expeditions undertaken by Alexander Mackenzie to discover a watercourse which would lead to the Pacific. In 1789 he travelled down an "unknown river until he perceived the rise and fall of the tide in the fog-bound delta. Although he is celebrated today for having discovered this major North American watercourse and for having made the return trip of 5000 km in a phenomenal 102 days, Mackenzie considered his expedition a failure. The river, after all, had not led to the Pacific." In 1793 Mackenzie paddled up the Parsnip River, and then made a difficult carry crossing over into the Fraser. Near the modern community of Alexandria, B.C., Indians advised him not to follow the Fraser but to go back upriver to where the West Road River flows into it. At that juncture, they trekked overland to reach the Pacific at the mouth of Bella Coola River. Mackenzie is "lionized for his speed and efficiency in penetrating new lands as he sought a route to the Pacific, condemned and celebrated for the way he drove men as he pursued his goals, the powerfully built Alexander Mackenzie had no illusions about why he was drawn to the unexplored tracts of Rupert's Land. Soon after completing his second historic journey, he candidly expressed his feelings toward the Athabasca district in a personal letter: "I think it unpardonable in any man to remain in this country who can afford to leave it." And leave it he did, returning to Britain for good in 1810.